1959
DOI: 10.2307/1929763
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Analysis of Dispersal in the Flour Beetle, Tribolum Confusum

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1964
1964
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…That this factor can nevertheless play an important role has recently been demonstrated for two species of Tribolium. Naylor (81,82) has shown that as density of adult beetles per unit volume of available flour increases, proportionately fewer adults enter the flour because of re pulsion from imaginal smell. Sonleitner (124) has shown that a growing proportion of the beetles leave the medium at increasing initial densities, probably because of the higher concentrations of the repellent ethyl quinone distributed in the medium by the beetles.…”
Section: The Deleterious Effects Of Competitionmentioning
confidence: 99%
“…That this factor can nevertheless play an important role has recently been demonstrated for two species of Tribolium. Naylor (81,82) has shown that as density of adult beetles per unit volume of available flour increases, proportionately fewer adults enter the flour because of re pulsion from imaginal smell. Sonleitner (124) has shown that a growing proportion of the beetles leave the medium at increasing initial densities, probably because of the higher concentrations of the repellent ethyl quinone distributed in the medium by the beetles.…”
Section: The Deleterious Effects Of Competitionmentioning
confidence: 99%
“…Furthermore, the number of adults found in vials of flour decreased with increasing larval density. The tendency of T. confusum to move to locations of unoccupied flour over occupied flour was also observed by Naylor [16].…”
Section: Density-dependent Dispersalmentioning
confidence: 55%
“…A major dispersal impetus in both Tribolium and O. surinamensis is poor food quality. For Tribolium dispersal, food quality seems to be more important than density (Naylor 1959(Naylor , 1961(Naylor , 1965. O. surinamensis dispersal accelerates rapidly with food depletion (Fig.…”
Section: Discussionmentioning
confidence: 99%